DELIBERATE SELF-POISONING IN SOUTH ODISHA: STUDY OF ITS CLINICAL PROFILE AND OUTCOME - NAYAK, SACHIDANANDA; BEHERA, BIJAYA KUMAR; BUDULA, KESHABA CHANDRA; ACHARYA, SRITAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Deliberate self-poisoning is a serious global issue that contributes to significant morbidity and mortality all over the world. The present study was conducted with an objective to identify the common agents used for self-poisoning prevalent in South Odisha and to determine the common clinical features and outcome of such cases. Methods: This cross-sectional observational study was conducted on 200 patients with deliberate self-poisoning belonging to the age group of 15–70 years over a period of 2 years from August 2017 to September 2019 in Maharaja Krishna Chandra Gajapati Medical College and Hospital, Berhampur, Odisha, India. All the above-mentioned patients admitted to the hospital, were treated with specific antidotes according to the poison ingested. Results were analyzed using appropriate standard statistical methods such as mean, standard deviation, and percentage. Results: Out of 200 patients, majority were female (65%, n=130) and 35% (n=70) were male; mean age was 38.9 (±16.8) years. Organophosphates, aluminum phosphide, glyphosate, organochlorines, and carbamates were the most common pesticides used as poisoning agents (74.5%, n=149) followed by plant poisons (7%, n=14) which included yellow oleander seed. Overall mortality in our study was 12.5%. Conclusion: Pesticides and plant poisons were the common agents used in our study for deliberate self-poisoning. Young persons, illiterates, and housewives were commonly involved in suicide attempts. Organophosphate caused majority of deaths.